The Role of Optical Surface Imaging Systems in Radiation Therapy - Hoisak, Jeremy D.P.; Pawlicki, Todd (Seminars in radiation oncology, 2018)
Optical surface imaging is a nonradiographic, noninvasive technology for continuous localization of patients during radiation therapy. Surface-guided radiation therapy (SGRT) has been applied to many treatment sites including breast, intracranial, head and neck, and extremities. SGRT enables a reduction of initial setup variability, provides verification of immobilization continuously during treatment including at noncoplanar linac gantry angles, and provides dynamic surface information for use in gated and breath-hold treatment techniques, all of which can permit reductions in the margins required to account for target localization uncertainty. Ancillary benefits from surface imaging include the ability to use immobilization techniques that confer greater comfort to patients, a reduction in imaging dose through reduced radiographic localization requirements, and improvements to the speed, efficiency, and safety of clinical workflows. This review will describe the objectives of SGRT, review the commercially available surface imaging systems, and provide an overview of SGRT applications by treatment site. Limitations and future applications of surfacing imaging systems are also discussed.